Density-optimized molybdenum alloy

JP2024116201A5Active Publication Date: 2025-03-11OTTO VON GUERICKE UNIV MAGDEBURG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024088113
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-06-05
Filing Date
2024-05-30
Publication Date
2025-03-11
Estimated Expiration
2039-06-04

AI Technical Summary

Technical Problem

Existing Mo-Si-B alloys used in high-temperature applications have a high density (8.5-9.5 g/cm³) which is not optimal for rotational or flight applications, particularly in aeronautics and space technology, and they lack sufficient toughness and oxidation resistance.

Method used

A ternary Mo-Si-B alloy system with 5 to 25 at.% silicon, 0.5 to 25 at.% boron, 3 to 50 at.% vanadium, and a molybdenum-vanadium mixed crystal matrix, incorporating at least one silicide phase, reduces density to less than 8 g/cm³ while maintaining oxidation resistance and toughness.

Benefits of technology

The alloy achieves a significant reduction in density, enhances strength, and maintains toughness and oxidation resistance, making it suitable for high-temperature structural components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide an alloy system based on Mo-Si-B that has a lower density than that of known Mo-Si-B alloy systems and accordingly can be utilized advantageously as a structural material for rotating or flying applications, in particular in aviation technology and aerospace technology, e.g., as a turbine material.SOLUTION: A molybdenum alloy has 5 to 25 atom% of silicon, 0.5 to 25 atom% of boron, and 3 to 50 atom% of vanadium, with the remainder consisting of molybdenum. The molybdenum alloy has a molybdenum-vanadium mixed crystal matrix and at least one silicide phase distributed therein. The density of the molybdenum alloy is less than 8 g / cm3.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a density-optimized and high-temperature resistant alloy based on molybdenum-silicon-boron (Mo-Si-B), its production method and its use as a structural material.

[0002] The ternary Mo-Si-B alloy system not only possesses an extremely high melting temperature (over 2000°C), allowing its use at temperatures significantly above 1000°C, but also excels in good oxidation resistance, outstanding creep resistance and sufficient ductile-brittle transition temperature and fracture toughness.

[0003] On the basis of these properties, the ternary Mo-Si-B alloy system is particularly suitable as a construction material for the manufacture of structural components operating at very high temperatures, such as turbine blades and disks in gas turbines, for highly stressed structural components in aeronautical and space technology, but also for tools in forming technology.

[0004] Particularly advantageous for the above-mentioned high-temperature applications is the very good oxidation resistance of this alloy system when the silicide proportion is greater than 50%. Protective measures to prevent oxidation, such as the use of protective gases or the application of protective layers, can therefore be omitted in the case of powder metallurgically produced or otherwise produced very fine-grained materials with grain sizes of less than 10 μm and a homogeneous phase distribution.

[0005] Pure molybdenum as a refractory metal has a melting point of 2623°C and is in principle suitable for high-temperature applications. However, a problem is its oxidation resistance, which is already low at temperatures above 600°C.

[0006] A significant increase in the oxidation resistance of molybdenum has been achieved by alloying it with silicon and boron and the associated formation of silicides. Oxidation-resistant ternary Mo-Si-B alloys of this type are described, for example, in EP 0 804 627 B1. At temperatures above 540° C., this ternary alloy system forms a boron-silicate layer, which prevents further penetration of oxygen into the solid or structural component.

[0007] DE 25 34 379 A1 relates to Mo-Si-B alloys, which may also contain, inter alia, vanadium. However, these are distinguished by high thermal stability, i.e. amorphous alloys which are stable even at high temperatures and do not start to crystallize.

[0008] DE 11 55 609 A likewise describes Mo alloys which contain as essential components at least one metal boride selected from chromium boride, titanium boride and zirconium boride and which may also have Si, B and V. None of the numerous examples explicitly mentioned contain V in addition to Mo. The aim here is exclusively to increase their oxidation resistance and strength, but not to improve toughness as desired according to the invention.

[0009] WO 2005 / 028692 A2 describes Mo-Si-B alloys that have Mo silicide and Mo-B silicide as essential components.Optionally, they may contain further elements that form mixed crystals with Mo, and in this case, Mo mixed crystals may be present, in which vanadium is mentioned among others.However, in this case, the one or more further elements are present exclusively in the mixed crystals, but not in the silicides.

[0010] According to US 2016 / 0060734 A1, the density of ternary Mo-Si-B alloys can be reduced by partial replacement of the heavy metal Mo with the apparently lighter metal Ti. However, it is pointed out that partial replacement of Mo with Ti impairs its oxidation resistance. To compensate for this, further elements, such as iron and / or yttrium, must be added.

[0011] With respect to the outstanding property profile shown above, this ternary Mo-Si-B alloy system could be a highly promising candidate as a structural material at high temperatures, e.g., as a turbine material, also for rotating or flight applications.

[0012] For this type of application, but also for other applications, the drawback here is typically a viscosity of 8.5 to 9.5 g / cm 3 For example, the alloy Mo-9Si-8B has a density of 9.5 g / cm 3 has a density of

[0013] The object of the present invention was therefore to provide an alloy system based on Mo-Si-B which has a lower density than the known Mo-Si-B alloy systems and can therefore be advantageously used as a structural material for rotating or flight applications, especially in aviation and space technology, for example as a turbine material, which should furthermore retain the advantages of the ternary alloy system Mo-Si-B, in particular with regard to its oxidation resistance.

[0014] This problem is solved by an alloy system having 5-25 atomic % silicon (Si), 0.5-25 atomic % boron (B), 3-50 atomic % vanadium (V) and the balance molybdenum, wherein the molybdenum alloy has a molybdenum-vanadium mixed crystal matrix and at least one silicide phase distributed therein, and the density of the molybdenum alloy is 8 g / cm 3 is less than.

[0015] According to a preferred embodiment, the molybdenum alloy has a vanadium content of 10 to 50 atomic % and at least one silicide phase selected from (Mo,V)3Si, (Mo,V)5SiB2 and (Mo,V)5Si3.

[0016] Preferably, the Mo content is more than 10 atomic %, in particular at least 20 atomic %, and particularly preferably at least 40 atomic %. The preferred content ranges are 8 to 15 atomic % for Si, 7 to 20 atomic % for B, and 10 to 40 atomic % for V.

[0017] Preferably, the alloy system according to the invention has a silicide phase proportion of at least 30% and in particular at least 50%.

[0018] Vanadium has a melting point of 1910°C, and therefore below 2000°C, and belongs to the so-called extended refractory metals, but has a density of 10.28 g / cm 3 At 293.15K, it has a higher density of 6.11 g / cm than molybdenum. 3 Vanadium has a distinctly lower density of 1. A further advantage of vanadium is that it has a similar atomic radius (134 pm) and the same crystal structure, i.e., body-centered cubic, as molybdenum (145 pm), which results in good miscibility and exchangeability of both elements in the crystal lattice and therefore good alloyability of both elements. Moreover, vanadium has high ductility, so its addition does not impair the toughness of the ternary Mo-Si-B alloy.

[0019] The alloy according to the invention with the addition of vanadium has in particular a melting point of 8 g / cm at 293.15 K. 3 has a density of less than .

[0020] It has been found that the alloyed vanadium dissolves in the respective Mo alloy and silicide phases, however, without changing the structural characteristics of the known phases in the Mo-Si-B alloy.

[0021] The ternary Mo-Si-B system has a Mo mixed crystal matrix which itself has good toughness, where boron is inserted in the interstitial sites and silicon in the superlattice sites in the Mo phase.

[0022] Additionally, silicide phases can be formed already during the pre-alloying, for example during very long and high-energy alloying processes or during powder atomization. At the latest, silicide phases arise during the compaction and / or heat treatment of the powder. These phases, especially Mo3Si (A15) and Mo5SiB2 (T2), do indeed impart high strength to the system, but reduce its toughness due to their brittleness. As the concentration of silicon and boron increases, the proportion of the silicide phase increases, which can form the matrix phase in the structure if a critical proportion (approximately 50% in the case of production by mechanical alloying processes) is exceeded. In addition to the reduction in toughness, a shift of the brittle-ductile transition temperature towards higher temperatures is expected to occur. Therefore, in order to avoid these disadvantages, it is aimed to produce alloys with Mo mixed crystal phase as matrix phase.

[0023] The addition of V not only prevents the toughness of the Mo-Si-B alloy from deteriorating, but also stabilizes the Mo mixed crystal phase, slightly increases the mixed crystal ratio, and improves the toughness of the entire system.

[0024] Moreover, the substitution of V atoms in the Mo mixed crystal lattice leads to further improvement in its strength.

[0025] As a result, it can be confirmed that the addition of vanadium to the ternary Mo-Si-B alloy system not only reduces the density, but also improves its strength while keeping the toughness unchanged. Moreover, the alloy system according to the invention has a structure in which the silicide phase is distributed in a Mo mixed crystal matrix, even with a silicide phase proportion of more than 50%, as a result of the addition of V.

[0026] According to a preferred embodiment, titanium (Ti) can be added to the Mo-Si-BV base alloy in an amount of 0.5 to 30 atomic %. It was confirmed that the addition of 0.5-10 atomic percent stabilizes the mixed crystal (Mo,V)3Si-(Mo,V)5SiB2 structure, and the addition of 10-30 atomic percent promotes the production of the four-phase alloy mixed crystal (Mo,V)3Si-(Mo,V)5SiB2-(Mo,V)5Si3. (Mo,V)5Si3 is the T1 phase. In addition, 4.51 g / cm 3 The addition of Ti, which has a density of only 1.0 μm, contributes to a further decrease in the density.

[0027] Optionally, the base alloy according to the invention may contain one or more additional alloying elements selected from the group consisting of Al, Fe, Zr, Mg, Li, Cr, Mn, Co, Ni, Cu, Zn, Ge, Ga, Y, Nb, Cd, Ca and La, each in a content between 0.01 atomic % and 15 atomic %, preferably up to 10 atomic %, and / or one or more alloying elements selected from the group consisting of HF, Pb, Bi, Ru, Rh, Pd, Ag, Au, Ta, W, Re, Os, Ir and Pt, each in a content between 0.01 atomic % and preferably at most 5 atomic %. The latter group is 9 g / cm 3 These are heavy elements that have a greater density and should be added in as little amount as possible to avoid increasing the density.

[0028] The aforementioned additional alloying elements may also be added in the form of their oxides, nitrides and / or carbides and composite phases (eg, oxynitrides) in concentrations up to 15% by volume of the alloy.

[0029] Constrained by the manufacturing technique, the alloy according to the invention may further contain interstitially soluble elements, such as oxygen, nitrogen, hydrogen. These are unavoidable impurities that cannot always be completely excluded from the process. However, these impurities are only present in the ppm range, typically less than 100 ppm.

[0030] The alloys according to the invention are non-eutectic alloys, but also near-eutectic alloys and eutectic alloys. Non-eutectic alloys are alloys that do not correspond to the stoichiometric composition of the eutectic. Near-eutectic alloys, on the other hand, are alloys that, in view of their composition, are close to the eutectic.

[0031] The production of the non-eutectic alloy according to the present invention is preferably carried out by powder metallurgical method technology. In this case, the powder mixture of the corresponding alloy components is processed by mechanical alloying, in which elemental powders as well as pre-alloyed powders can be used. For this mechanical alloying, various high-energy mills can be used, such as attritors, drop ball mills, vibratory mills, planetary ball mills. In this case, the metal powder is subjected to intensive mechanical processing and homogenized to atomic level. The pre-alloying can alternatively also be carried out by an atomization process under protective gas.

[0032] The mechanically alloyed powder can then be consolidated by FAST (Field Assisted Sintering Technology). A suitable FAST process is, for example, performed under vacuum at 1600°C with a pressure of 50 MPa and a holding time of 15 minutes, with heating and cooling at 100 K / min. Alternatively, the powder can also be consolidated by cold isostatic pressing, e.g. sintering at 1600°C, and hot isostatic pressing (HIP) at 1500°C and 200 MPa. However, the FAST process is preferred since the process time during sintering is significantly reduced compared to hot pressing.

[0033] Moreover, homogeneous material properties can be achieved even in the case of larger structural components. Also, higher strengths and hardnesses, expressed here as microhardness, can be obtained with FAST, because grain growth during the process is prevented due to the significantly shorter process times. Fine grains in the structure result in better strength than coarser grains.

[0034] Alternatively to powder metallurgical processes, the density-optimized alloys according to the invention can be produced by additive manufacturing methods, such as selective laser melting (SLM) or laser metal deposition (LMD), which here are based on mechanically alloyed or atomized and thus pre-alloyed powders, which, due to the alloying of V (and possibly Ti or other alloying elements), have a reduced melting point with respect to the pure ternary Mo-Si-B alloys and are therefore more easily processable by such methods.

[0035] The advantage of additive manufacturing is that it allows for near-final structural components to be obtained in a cost-, time- and material-efficient manner. Additive manufacturing methods of this kind are known per se and are described, for example, in WO 2016 / 188696 A1.

[0036] Near-eutectic and eutectic alloys can be processed particularly well by additive processes, since particularly fine-grained structures having good mechanical strength can be produced. Such alloys are within the composition range Mo-(7..19)Si-(6...10)B-(5...15)V or Mo-(7..19)Si-(6...10)B-(5...15)V-(5...18)Ti. Furthermore, these alloys are also suitable for other melt metallurgical processes, in particular for directional solidification in the known Bridgman process.

[0037] The alloy system according to the invention is characterized in more detail below on the basis of examples and figures. [Brief description of the drawings]

[0038] [Figure 1] The X-ray diffraction pattern of the alloy sample MK6-FAST (Mo-40V-9Si-8B) is shown; [Diagram 2] 2 shows the microstructure of the alloy sample MK6-FAST according to FIG. 1 after consolidation by the FAST method, shown as a binary image; and [Diagram 3] 4 shows the results of microhardness testing taking into account the standard deviation of alloy samples according to the embodiment.

[0039] A) Sample preparation 1. mechanical alloying Four alloys with 10, 20, 30 and 40 atomic % vanadium were produced. The atomic contents of silicon (9 atomic %) and boron (8 atomic %) remained the same for all alloy systems. 30 g were produced from each alloy system. For this purpose, the individual alloy components were weighed out under an argon protective gas atmosphere and transferred into a grinding vessel in a protective gas atmosphere. The resulting powder mixture was ground in a planetary ball mill (type PM 4000) from Retsch GmbH using the following parameters: [Table 1] The resulting alloys were given the following designations: [Table 2]

[0040] 2. Heat Treatment The alloy obtained in step 1 was heat treated. The samples were each transferred into a ceramic dish and annealed under argon protective gas for the entire duration of the heat treatment. For this purpose, approximately 10 g of each of the alloys present in the initial state were transferred and heat treated at 1300° C. for 5 hours in a tube furnace of the type Losic of the HTM Retz GmbH.

[0041] The resulting samples were given the following designations: MK3-WB, MK4-WB, MK5-WB and MK6-WB

[0042] 3. Preparation of alloy samples by FAST Sample MK6-WB was consolidated by FAST by heating and cooling at 100 K / min under vacuum at a pressure of 50 MPa and holding times of 10 min at 1100° C. and 15 min at 1600° C. The resulting sample was given the designation MK6-FAST.

[0043] B) Structural survey 1. X-ray diffraction method (XRD) Structural investigation of the samples MK3-WB, MK4-WB, MK5-WB, MK6-WB and MK6-FAST ground into powder was carried out by X-ray diffraction analysis using the X-ray diffractometer system PANalytical X'pert pro: - Radiation:Cu-K21,21,5406 - Voltage: 40kV - Current: 30mA - Detector: X' Celerator RTMS - Filter: Ni filter - Measurement range: 20°≦2Θ≦158.95° - Step width: 0.0167° - Measurement time 330.2s (per step width).

[0044] In all five samples, the phases Mo-V mixed crystal, (Mo,V)3Si and (Mo,V)5SiB2 were detected. The results of the analysis for MK6-FAST are shown in FIG.

[0045] 2. Texture investigation and density measurement The microstructure and morphology of the powder particles were analyzed using a Philips ESEM (SEM) XL30 scanning electron microscope. The phase contrast was visualized by BSE contrast. The phases involved were assigned by EDX analysis.

[0046] For the sample preparation, a small amount of the sample powder was cold embedded in epoxide resin as follows, followed by wet grinding with SiC abrasive papers having grit sizes of 800 and 1200 and polishing with a diamond suspension. For the SEM investigations, the samples were sputtered with a thin layer of gold before the embedding.

[0047] The structure of the alloy MK6-FAST is shown in binarized form in Figure 2, where the Mo alloy phase is white and both silicide phases are black.

[0048] The density of MK6-FAST is 7.8g / cm according to Archimedes' principle. 3 was measured.

[0049] C) Evaluation 1. SEM / EDX analysis The EDX analysis confirmed the results of the XRD measurements: in addition to the Mo mixed crystal, the silicide phases (Mo,V)3Si and (Mo,V)5SiB2 were formed in the structure of all samples, with a higher proportion of vanadium being found in the silicide phase than in the mixed crystal matrix.

[0050] Evaluation of MK6-FAST revealed that it had the highest percentage of silicide phase in the structure compared to the heat treated samples.

[0051] The following table summarizes the percentage (atomic %) of the silicide phase in each of the samples. [Table 3]

[0052] 2. Microhardness Testing Measured were the microhardness of the mechanically alloyed (ML) samples MK3, MK4, MK5, MK6 and MK6-FAST.

[0053] The microhardness was measured by the Vickers method using a microscope (type Axiophod 2) from Carl Zeiss Microscopy GmbH, which was integrated with a hardness tester (type MHT-10) from Anton Paar GmbH: - Test load: 10p - Test time: 10s - Tilt: 15 p / s.

[0054] The samples were prepared as for the SEM analysis (see B.2.) but without gold sputtering.

[0055] 50 indentations per phase were made and evaluated.

[0056] The results, taking into account the standard deviation, are shown in FIG. The microhardness of the silicides in the FAST specimen is significantly higher than that of the mixed phases. The extremely fine and homogeneous distribution of the silicide phases and their proportion of about 55% ensures the high overall hardness of the alloy. The overall hardness of the FAST specimen is synthesized from the microhardness of each of the individual phases, the Mo,V mixed phase and the two silicide phases.

Claims

1. 1. A molybdenum alloy having 5 to 25 atomic percent silicon, 0.5 to 25 atomic percent boron, and 30 to 40 atomic percent vanadium, with the balance molybdenum, wherein the proportion of molybdenum is at least 40 atomic percent; The molybdenum alloy has a molybdenum-vanadium mixed crystal matrix and at least one silicide phase distributed therein, and the density of the molybdenum alloy is 8 g / cm 3 and the at least one silicide phase is less than (Mo, V) 3 Si, (Mo, V) 5 SiB 2 And (Mo, V) 5 S 3 and having a silicide phase percentage of at least 30%.

2. The molybdenum alloy of claim 1, wherein silicon is present in an amount of 8 to 15 atomic % and / or boron is present in an amount of 7 to 20 atomic %.

3. A molybdenum alloy as described in claim 1 or 2, further containing titanium (Ti) in an amount of 0.5 to 30 atomic %.

4. The molybdenum alloy of claim 3, wherein the Ti content is 10 to 30 atomic %.

5. The molybdenum alloy of claim 3, wherein the Ti content is 0.5 to 10 atomic %.

6. The molybdenum alloy according to any one of claims 1 to 5, further comprising one or more alloying elements selected from the group consisting of Al, Fe, Zr, Mg, Li, Cr, Mn, Co, Ni, Cu, Zn, Ge, Ga, Y, Nb, Cd, Ca, and La, each in a content of 0.01 atomic % to 15 atomic %, and / or one or more alloying elements selected from the group consisting of Hf, Pb, Bi, Ru, Rh, Pd, Ag, Au, Ta, W, Re, Os, Ir, and Pt, each in a content of 0.01 atomic % to 5 atomic %.

7. A molybdenum alloy according to claim 1, wherein the proportion of silicide phase is at least 46%, preferably at least 50%.

8. A molybdenum alloy according to claim 1, wherein the alloy has a structure having a Mo-V mixed crystal matrix and (Mo,V) 3 Si and / or (Mo,V) 5 SiB 2 distributed therein.

9. The molybdenum alloy of claim 8, further comprising the phase (Mo,V) 5 Si 3 present.

10. A method for producing the molybdenum alloy according to any one of claims 1 to 9, comprising the steps of: The process, wherein the starting elements are mechanically alloyed in a first step and subsequently consolidated in a second step by FAST (electric field assisted sintering technique) or by hot isostatic pressing.

11. Use of a molybdenum alloy according to any one of claims 1 to 9 as a structural material for rotating or flight applications, in particular in aeronautical and space technology.

12. Use of the molybdenum alloy according to claim 11 as a turbine material.